A COMPARATIVE STUDY OF AIRLINE COMPANIES FROM THE SOCIAL RESPONSIBILITY PERSPECTIVE CASE STUDY - Taghizadeh, Houshang; Shokri, Abdolhossein (PEOPLE: International Journal of Social Sciences, 2015)
Responding to or satisfying the demands of the external beneficiaries including customers, suppliers, distributors, environmentalists, and the residents of the productive or service-giving activity location, while preserving the benefits of the internal beneficiaries including the owners or share-holders and the personnel of the organization is known as social responsibility. The present research has been carried out with the purpose of comparing the Islamic Republic of Iran Airline Companies from the viewpoint of social responsibility. The research method is descriptive, and statistical population includes customers who travel at least five times monthly with various IRI Airline companies, including 150 individuals. Due to the limitedness of the population, no sampling was carried out. A researcher- devised questionnaire was used for data collection. The validity of the questionnaire was confirmed by content validity, and its reliability was evaluated through the use of Cranach Alpha coefficient based on Carroll’s approach. For data analysis, the researchers made use of TOPSIS method and Shannon’s Entropy. The results indicate the rank of each company with regard to the rate of attention paid to corporate social responsibility.